Role of Metaphors in Communicating the Threat of Climate Change - Manuja Jayasundara; Christine Overdevest; Olesya M. Savchenko; Martha C. Monroe (The Journal of Public Interest Communications, 2026)
Climate change is a threat to both human societies and natural ecosystems. Yet, for public interest communications, debate persists over whether metaphors meaningfully shift public risk perceptions and policy support. Using data from a U.S. survey experiment (N = 859) recruited via Amazon’s Mechanical Turk, we tested the effects of metaphorical (war, race) and nonmetaphorical (“issue”) messages, relative to a no-information control, on risk perception, urgency, and policy support. War and race metaphors did not produce effects that differed significantly from the nonmetaphorical issue frame. In contrast, political ideology and demographics were stronger and more consistent predictors of climate attitudes than message framing. These findings suggest that audience characteristics may matter more than metaphor choice for climate communication.